2021
DOI: 10.2174/1567202618666211013123557
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cardiometabolic Index and Stroke: A Population- based Cross-sectional Study

Abstract: Background: Cardiometabolic index (CMI) is associated with several risk factors for stroke; however, few studies have assessed the role of CMI in stroke risk. Objective: This study aimed to assess the association between CMI and stroke in a population-based cross-sectional study. Methods: This study included 4445 general residents aged ≥40 years selected by multistage stratified random cluster sampling. CMI was calculated as the product of the ratio of waist circumference to height (WHtR) and the ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…CMI is the binding product of TG/HDL-C ratio and WHtR. It has been shown to be closely associated with diabetes, cardiovascular disease, stroke, metabolic syndrome and kidney disease [10][11][12][13][14]. For the relationship between NAFLD and CMI, we found that the CMI value in the NAFLD group was signi cantly higher than that in the Non-NAFLD group.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…CMI is the binding product of TG/HDL-C ratio and WHtR. It has been shown to be closely associated with diabetes, cardiovascular disease, stroke, metabolic syndrome and kidney disease [10][11][12][13][14]. For the relationship between NAFLD and CMI, we found that the CMI value in the NAFLD group was signi cantly higher than that in the Non-NAFLD group.…”
Section: Discussionmentioning
confidence: 68%
“…It is calculated by multiplying the lipid ratio triglyceride (TG)/ high-density lipoprotein cholesterol(HDL-C) by the waist-to-height ratio(WHtR) [9]. CMI was further found to be closely associated with CVD, stroke, MetS, and kidney disease [10][11][12][13][14]. The importance of changes in blood lipids and obesity is self-evident for NAFLD, and waist-height ratio is more likely to identify NAFLD patients with abdominal obesity than BMI [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed as a predictive tool for assessing risks associated with type 2 diabetes and cardiovascular diseases 7 . Studies have identified correlations between the CMI and conditions such as hyperuricaemia, obstructive sleep apnoea, and stroke 8 10 . Given the promising diagnostic capability of the CMI for various metabolic disorders, its potential role in NAFLD diagnosis warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its integrated abdominal obesity and dyslipidemia indices, CMI was validated to be a robust and independent clinical adiposity discriminator as well as a closer correlation with metabolic abnormality than traditional anthropometric indicators (11,12). Additionally, prior CMI-related studies have demonstrated that CMI can detect the presence of obesity-related disorders and cardiovascular dysfunction, including diabetes, hyperuricemia, nonalcoholic fatty liver disease, hypertension, stroke, kidney disease, erectile dysfunction, and peripheral arterial disease (10,(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%